The University of Georgia - Higbee, Jeanne L.; Dwinell, Patricia L. (Washington, D.C. : Distributed by ERIC Clearinghouse, 1991)
This paper describes the development of the University of Georgia's Division of Developmental Studies--a program providing special developmental instruction to students who otherwise would not have been admitted to the school. It consists of four components: English, mathematics, reading, and counseling. The objectives of each of these components are presented. The report then discusses the program's development, goals, and objectives; the results and outcomes for students and the institution; resource allocation; and its potential for adaptation by other institutions. Among the information presented is the following: (1) between 85 and 90 percent of students matriculating in the program fulfill the requirements needed to go on to regular university work; (2) students from the program also persist at rates comparable to those of first-time entering freshmen; (3) although SAT (Scholastic Aptitude Test) and high school grade point averages are lower for students entering the program, results show no significant differences in their academic performance compared to other students in introductory English, mathematics, and social science courses; and (4) 46.1 percent of the students who completed the program graduated from the university, compared to 59.5 percent for all freshman matriculants. The appendix, which comprises most of the document, includes exit criteria, an annual breakdown of enrollment into the program since 1981 and an example of a weekly progress report. (GLR)
ERIC Note: Paper presented at the National Conference on Student Retention (New York, NY, July 1991).
Educational level discussed: Higher Education.
Educational level discussed: Postsecondary Education.
Administrators.
Practitioners.
Microfiche.
Keywords: Academic Achievement